Surviving Inaagosto household strategies to cope with the lean season in a community in Batangas province - Dalisay, Soledad Maninang (2003)
This study attempted to describe the coping strategies to provide food for the family of low-income households in Barangay Ambulong, Tanauan City. Jerome, Pelto and Kandell's (1980) Ecological Model on Nutritional Anthroplogy was used to develop an analytical framework for this study. Data were collected for one-year period and two rounds of interviews were done-once during the abundant food season and another during the lean food season. Initially, 56 purposively sampled households participated in the study. Half had employed wives and another half had unemployed wives. During the second round of data collection, however, only fifty-three households remained. Methods of data collection included the semi-structured interview with the wife and/or the husband as the respondents, forced scale, anthropometry of 0 - 5 year old children, life history of selected informants, focus group discussion among barangay health workers, household food consumption interview, observations, and use of secondary data. Data were analyzed using means and percentages. Diet diversity scores were computed. The Chi-Square was computed to determine association between maternal employment and anthropometroc measurements of the children. Majority of the respondents were engaged in unskilled labor. Average annual per capita income of all households was PhP 15,525.74. Average monthly expenditures on food were greater than expenditures on non-food items. Anthropometric survey among the 0-5 year old children showed that although the nutritional status of the majority of the children was normal, a third of the children had below normal nutritional status based on International Reference Standards. Chi-Square tests revealed that there was no association between maternal employment and nutritional status of the children. The diet diversity scores showed that there was only a slight difference between food consumption during the abundant and the lean seasons. The lean season in the barangay coincided with the rainy months that started in June, peaked in August, and ended in November. The peak of the lean month was called inaagosto. the abundant months coincide with the dry months that started and peaked in December and ended in May. The study identified local economic, nutritional and health indicators of food security. Coping strategies employed by the respondents were classified as economic, social, and nutritional. Some of the strategies referred to in the study were considered as "functional deviations" because these did not conform to the community's expected behavior but nonetheless, helped households to survive. Coping was seem to be female- focused. The study presented recommendations that aimed to provide directions for the development of more appropriate programs to ensure household food security.